Cartilha do Araguaia “... Estou lendo!!!” : seu circuito de comunicação (1978 -1989) - Rodrigues, Alessandra Pereira Carneiro (2012)
This ongoing study at the Post-Graduation Program in Education at UFMT/Rondonópolis, state of Mato Grosso, Brazil, ALFALE research group, is related to reading and school books history field and is based on the “communication circuit”, a model proposed by Robert Darnton (1990), so that books can be analyzed. This paper aims to: 1) analyze the life cycle of the school book “... Estou Lendo!!!” (I‟m Reading!!!), by means of a model proposed by Darnton (1990) and 2) salvage and analyze the elements that compose the set of the regional course book “...Estou Lendo!!!” (I‟m Reading!!!). Prior studies point out that the state of Mato Grosso is mostly a consumer than a producer market of school course books. Therefore, once having in hand a regional course book, organized by mato-grossense authors (that is, those ones born in the state of Mato Grosso), it highlights how worthwhile it is the source it is herein researched. From the methodological point of view, such study uses ordinary procedures in the historic driven researches, consisting in finding, meeting, organizing and analyzing the oral and documental sources, which may help to comprehend aspects of the object under investigation. It is a historical background research, which is after subsidies in both Cultural History and Book History fields. This research is based on the following writers/thinkers, related to cultural history (BURKE, 2005; LE GOFF, 2001 and CHARTIER, 1990), school culture (JULIA, 2001), Education history (LOPES; GALVÃO, 2001), book history (DARNTON, 1990; CHOPPIN, 2004 and BITTENCOURT, 2008) and to the literacy field (TFOUNI, 2010; KLEIMAN, 1995 and SOARES, 2010). Since it is about a regional course book, this very research is based on studies by mato-grossense regional historiography scholars (AMÂNCIO, 2008, CARDOSO; AMÂNCIO, 2005 and CARDOSO, 2009). The temporal demarcation of this research focuses on the years 1978 to 1989. In 1978 the “Elementary School In-Class Performance Human Resources Training Course” was offered in the region – a summer course, designed for lay teachers, fact regarded as the beginning of the course book “...Estou Lendo!!!” (I‟m Reading!). The year 1989 brings the end of the periodization, based on data collected through written sources. The analyzes show a nationwide context in which the educational failure stands out, especially when moving from the first grade to the second one in elementary school, which is faced by public policies supplied by the Education Ministry as well as the state and municipal secretariats of education. In the regional context, the municipality of São Félix do Araguaia, in the state of Mato Grosso, the performance by its Prelacy, managed by bishop Pedro Casaldáliga Pla, is on the spotlight, in a historical moment of fights for land possession. From the educational point of view, the church and the state are united in the proposition of offering a training course for in-class teachers, adopting Paulo Freire‟s perspective regarding emancipatory literacy. It is in such context that arises the course to be analyzed. The data brings evidence that the literacy teachers in the Araguaia region, inserted in a political struggle context, can be considered pioneers, back in early 1984, in developing schooling practices which involve the very act of teaching of spelling and literacy, possible to be seen in the course book/literacy book “...Estou Lendo!!!” (I‟m Reading!).